2020
DOI: 10.3390/agronomy10040583
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 16 Peanut (Arachis hypogaea L.) CSSLs Derived from an Interspecific Cross for Yield and Yield Component Traits: QTL Validation

Abstract: Cultivated peanut is an allotetraploid (2n = 4× = 40) with narrow genetic diversity. In previous studies, we developed an advanced backcross quantitative trait loci (AB-QTL) population from the cross between the synthetic allotetraploid ((Arachis ipaensis × Arachis duranensis)4×) and the cultivated variety Fleur11, and mapped several quantitative trait loci (QTLs) involved in yield and yield components. We also developed a chromosome segment substitution line (CSSL) population as a way to mendelize the QTLs an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 67 publications
(82 reference statements)
0
13
0
Order By: Relevance
“…The magnitude of the genotypic variance indicates that are significant variations within peanut varieties in terms of pod and seed weight and kernel ratio. High values of broadsense heritability were reported for seed weight (87-93%), 100-pod weight (88-91%), pod yield (71-74%) and 100kernel weight (87-96%) by Tossim et al (2020). Rao et al (2014) reported high heritability for shelling percentage (92.2%), pod number (76.9%), kernel weight (97.4%) and pod yield (95.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The magnitude of the genotypic variance indicates that are significant variations within peanut varieties in terms of pod and seed weight and kernel ratio. High values of broadsense heritability were reported for seed weight (87-93%), 100-pod weight (88-91%), pod yield (71-74%) and 100kernel weight (87-96%) by Tossim et al (2020). Rao et al (2014) reported high heritability for shelling percentage (92.2%), pod number (76.9%), kernel weight (97.4%) and pod yield (95.5%).…”
Section: Resultsmentioning
confidence: 99%
“…The authors hypothesized these regions as a target of human selection during peanut domestication. More recently, using the CSSL population, Tossim et al [14] confirmed the QTL in the proximal region of chromosome A07 carried by the line 12CS_091 as involved in pod and seed size variation.…”
Section: Introductionmentioning
confidence: 88%
“…Genotypically, this CSSL differs from Fleur11 by the introgression of a segment of A. duranensis chromosome in the proximal region of the chromosome A07 relative to the published genome sequence. Phenotypically, it has smaller seeds than Fleur11 [14]. From these parents, a large F 2 population of 2172 individuals was developed by single cross followed by self-pollination of the F 1 generation.…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Advances in genetics and genomics offer opportunities to dive into feral peanut diversity to mine new alleles for breeding [ 35 , 36 ]. Interspecific mapping populations such as advanced backcross (AB-QTL) and chromosome segment substitution lines (CSSLs) were developed and used in peanuts to identify several QTLs related to yield components, disease resistance, oil quality, and plant morphology [ 37 , 38 , 39 , 40 ]. However, to our knowledge, interspecific mapping populations have not been exploited to investigate the effect of wild species alleles on BNF.…”
Section: Introductionmentioning
confidence: 99%